Towards a new standard : theoretical and empirical studies on the restandardization of Italian - Cerruti, Massimo; Crocco, Claudia; Marzo, Stefania (Language and social life (Mouton de Gruyter) ;, 2017)
In many European languages the National Standard Variety is converging with spoken, informal, and socially marked varieties. In Italian this process is giving rise to a new standard variety called Neo-standard Italian, which partly consists of regional features. This book contributes to current research on standardization in Europe by offering a comprehensive overview of the re-standardization dynamics in Italian. Each chapter investigates a specific dynamic shaping the emergence of Neo-standard Italian and Regional Standard Varieties, such as the acceptance of previously non-standard features, the reception of Old Italian features excluded from the standard variety, the changing standard language ideology, the retention of features from Italo-Romance dialects, the standardization of patterns borrowed from English, and the developmental tendencies of standard Italian in Switzerland. The contributions investigate phonetic/phonological, prosodic, morphosyntactic, and lexical phenomena, addressed by several empirical methodologies and theoretical vantage points. This work is of interest to scholars and students working on language variation and change, especially those focusing on standard languages and standardization dynamics.